2022
DOI: 10.1186/s42238-021-00111-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term environmental stresses on the onset of cannabinoid production in young immature flowers of industrial hemp (Cannabis sativa L.)

Abstract: Backgrounds Cannabis sativa L. produces at least 120 cannabinoids. Although genetic variation is the main factor in cannabinoid production, the effects of short-term environmental stresses in the early flowering stage remains largely unknown. Methods To investigate the effects of short-term environmental stresses on the onset of cannabinoid production in young immature flowers, a hemp variety, Green-Thunder (5–8% CBD/mg of dry weight), was treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…CBG is a shared precursor molecule to the production of both CBD and THC. The increase of CBG accumulation, resulting in accumulation of cannabigrolic acid (CBGA) that was decarboxylated under stress conditions (Park et al . 2022).…”
Section: Resultsmentioning
confidence: 99%
“…CBG is a shared precursor molecule to the production of both CBD and THC. The increase of CBG accumulation, resulting in accumulation of cannabigrolic acid (CBGA) that was decarboxylated under stress conditions (Park et al . 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the presence of a different mite species, twospotted spider mites ( T. urticae ), on hemp had the opposite effect, leading to an increase in CBD and THC levels (Kostanda and Khatib 2022). Tobacco hornworm infestation, however, is more similar to HRM in that cannabinoid levels, specifically CBD and CBGA, were reduced relative to healthy plants (Park et al 2022). These results highlight the need for further investigation into the role of cannabinoids and other specialized metabolites in multiple pest species to understand the full spectrum of the effects.…”
Section: Discussionmentioning
confidence: 99%
“…21 The results revealed that cultivar type significantly influences the flower yield and total cannabinoid content, with Cherry Blossom yielding a high flower yield and Cherry XT1 showcasing the highest cannabinoid production. Several other studies have highlighted cultivar type, 22,23 environmental stress, 24 genotype, 25 and genotype × environment interactions 26 as important factors influencing hemp flower yields and bioactive compound production. However, the studies focusing on the influence of production practice on the hemp flower yield, cannabinoid content, and volatile profile are far from adequate.…”
Section: Introductionmentioning
confidence: 99%